GENDER EQUALITY IN ISLAMIC FAMILY LAW: Breaking the Chain of Domestic Violence to Achieve Harmonious Family - Mufidah Cholil; Sudirman Sudirman (Kafa`ah: Journal of Gender Studies, 2019)
This paper describes some efforts to build gender equality in Islamic law against domestic violence. Family is the smallest institution in society as a mirror of a nation. Nevertheless, family problems continue to occur, including domestic violence. Domestic violence is a classic problem in a family resulting in caring for family functions to realize harmonious family. Based on the data collected, the number of women victims of domestic violence is still high, due to gender relations with patriarchal culture.  This situation is legitimized by the sacred text which is still considered gender bias, such as in Islamic family law. Therefore, Islamic family law reform is obviously needed by discussing the concept of sakīnah (harmonious) family with gender equality through formal legal approach, legal culture, uṣūl fiqh (philosophy of Islamic law), and al-maqāṣid al- syarī'ah (the purposes of Islamic Law) and universal Islamic values as raḥmah li al-‘ālamīn (blessing for the universe) to establish harmonious family.